Mental health of college students and associated factors in Hubei of China. - Xiaosheng Lei (Public Library of Science (PLoS), 2021)
Background Although many studies have analyzed mental health problems in college students in China, the associations of mental health with individual and family circumstances, academic performance, and social support were rarely discussed. Objectives The study aimed to determine the mental health status and its associated factors among college students in China. Methods An online survey was conducted on 300 students selected through a cluster sampling strategy in a university in Hubei, China, tapping into sociodemographic characteristics of the participants, their mental health status measured by the modified Symptom Checklist-90 (SCL-90), and social support measured by the Social Support Rating Scale. Multivariate linear regression models were established to identify predictors of the SCL-90 scores. Results Mental health disorders were found in 8% of the respondents, with obsessive compulsive, interpersonal sensitivity and depression as the top three reported problems. Compared with the national population norms of university students in 2014, our study participants had higher scores in SCL-90. There were statistically significant difference in the Global Severity index (GSI) and all nine subscales scores (p<0.05). Poorer self-rated health, higher study pressure, and lower social support were significant predictors of higher SCL-90 scores (p<0.05) after adjustment for variations in other variables. Conclusions College students in Hubei, China may experience a range of different mental health problems, which are associated with their individual, study, and social circumstances.